Factors Related to The Occurrence of Risiko Pregnancy During the COVID-19 Pandemic in Pregnant Women - Ningsih, Yulianti; Lamri, H.; Suryani, Heni (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: The high maternal mortality rate i largely due to risk pregnancy. 90% of maternal deaths occur at the time of delivery and immediately after delivery. The direct causes of maternal mortality include bleeding at 28%, eclampsia at 24% and infection at 11%. While the indirect causes are Chronic Energy Deficiency during pregnancy 57%, anemia in pregnancy 40%. Risk pregnancy is a pregnancy that can cause pregnant women and babies to become suspected of death or die before birth takes place. Factors that affect the high maternal mortality rate are age, knowledge and parity. Methods: This study used a cross sectional design.  The study population is all pregnant women in the first, second and third trimesters who visited the Linggang Bigung Health Center. Results and Discussion: Most of the respondents had 32 (59.3%) risk-free age (20-35 years), 37 (68.5%) risk-free parity (2-3 children), 30 people (55.6%) had sufficient knowledge and 31 (57.4%) had high-risk pregnancies. The results of the Sperm Corelation  test were obtained from the age factor (value p=0.001), the knowledge factor (value p=0.001) and the parity factor (value p=0.017), where these three factors were related to pregnancy risk. Conclusion: Age factors, knowledge factors and parity factors are related to pregnancy risk at Linggang Bigung Health Center